Mechanics of pole vaulting: a review - Frere, J.; L'Hermette, M.; Slawinski, J.; Tourny-Chollet, C. (Sports Biomechanics, 2010)
A good understanding of the mechanics of pole vaulting is fundamental to performance because this event is quite complex, with several factors occurring in sequence and/or in parallel. These factors mainly concern the velocities of the vaulter-pole system, the kinetic and potential energy of the vaulter and the strain energy stored in the pole, the force and torque applied by the athlete, and the pole design. Although the pole vault literature is vast, encompassing several fields such as medicine, sports sciences, mechanics, mathematics, and physics, the studies agree that pole vault performance is basically influenced by the energy exchange between the vaulter and pole. Ideally, as the athlete clears the crossbar, the vaulter mechanical energy must be composed of high potential energy and low kinetic energy, guaranteeing the high vertical component of the vault. Moreover, the force and torque applied by the vaulter influences this energy exchange and these factors thus must be taken into consideration in the analysis of performance. This review presents the variables that influence pole vault performance during the run-up, take-off, pole support, and free flight phases.